From Shooting to Shopping: Randall Davidson’s Attitudes to Work, Rest, and Recreation - Mews, Stuart (Studies in church history, 2002)
If Jose Harris was right when she asserted that ‘there was no such thing as a homogeneous Victorian work ethic’ and that a history of work, especially between 1870 and 1914, can only be written on the basis of the reported observations of, and reflections on, the work of individual farms, factories, homes, offices, and workshops, she would find few better sources than the astonishing variety of personal experiences and insights of Randall Davidson (1846-1930), England’s longest-serving Archbishop of Canterbury. Davidson’s early career touched a range of contacts from middle-class urban Edinburgh, to the Lowland small country estate, English public school, and Oxford college; as well as the doctor-dominated private sickroom, smart shooting parties on grouse moors, the staid Lambeth Palace bureaucracy, the tradition-infested Court at Windsor, the arcane Board of the British Museum, and the privileged confines of the House of Lords and West End clubs with their opportunities for strategic socializing and quiet persuasion. At the same time there was a coming to terms with the new consumer society as manifested in the new shopocracy of retail stores like Debenhams. These different worlds imposed their own power-structures, work expectations, and demands on both providers and purchasers. They produced their own stresses and strains which called for mitigation. The huge range of what constituted work was part of the concerns of the socially-alert clergyman in late Victorian Britain, none more so than Randall Davidson, who can be profitably considered as an exponent of, participant in, and observer of the place of work and use of time in his society.